2016
DOI: 10.1037/adb0000123
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to electronic nicotine delivery systems (ENDS) visual imagery increases smoking urge and desire.

Abstract: Use and awareness of electronic nicotine delivery systems (ENDS; also known as electronic cigarettes or e-cigarettes) has increased rapidly in recent years, particularly among young adults. As use of ENDS resembles traditional smoking in both hand to mouth movements and inhalation and exhalation behaviors, we determined whether exposure to e-cigarette use via video exposure would act as a cue to elicit urge and desire for a combustible cigarette. Young adult smokers (mean age 26.3 ± 4.1 years) were randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 50 publications
(56 reference statements)
5
40
6
Order By: Relevance
“…The lack of e-cigarette cue effects conflicts with results from previous experiments with smokers that found that e-cigarette images increased smoking urges 28 and sparked immediate smoking. 14 Because our measures of these outcomes were either identical or comparable to those in these previous studies, this leads us to speculate that the differences in results may be due to differences in stimuli.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…The lack of e-cigarette cue effects conflicts with results from previous experiments with smokers that found that e-cigarette images increased smoking urges 28 and sparked immediate smoking. 14 Because our measures of these outcomes were either identical or comparable to those in these previous studies, this leads us to speculate that the differences in results may be due to differences in stimuli.…”
Section: Discussioncontrasting
confidence: 98%
“…In contrast to the print ads and 40-second total duration of exposure in our study, previous studies used video ads with stimuli exposure durations ranging from one minute to 4 or more minutes. 14,28 The longer duration of exposure and more vivid nature of the video ads may have resulted in a greater dose of the e-cigarette cue and, in turn, greater effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an experimental study among young-adult tobacco smokers reported that exposure to a video showing vaping significantly increased their urge to smoke as well as their desire for tobacco cigarettes and e-cigarettes 4 . Similarly, another experimental study found that exposure to the e-cigarette cue but not the tobacco cigarette cue also significantly increased desire to smoke an e-cigarette 5 …”
Section: Arguments For Prohibiting Vapingmentioning
confidence: 99%
“…Given that smoke-free policies have been important drivers of smoking reduction and cessation,21 it is plausible that being able to vape in public places may in fact dampen decisions to quit or lead to relapse for many. Indeed, experimental evidence suggests that exposure to ENDS advertising22 23 and imagery24 may stimulate smokers and ex-smokers to try ENDS, smoke more cigarettes or relapse to smoking 16 17…”
Section: Helping Smokers Quit Versus Triggering Relapse In Former Smomentioning
confidence: 99%